Coseismic and postseismic deformation from the 2007 Bengkulu earthquake based on GPS Data - Irwan Meilano; Susilo Susilo; Endra Gunawan; Suchi Rahmadani (Indonesian Institute of Sciences, 2021)
On September 12, 2007, a M8.5 megathrust earthquake occurred along the Sunda trench near Bengkulu, West Sumatra. GPS data in Sumatra have indicated the coseismic and postseismic deformations resulting from this earthquake. Our estimate of coseismic displacements suggests that the earthquake displaced up to 1.8m at GPS stations located north of the epicenter. Moreover, our principal strain estimation in the region suggests that the maximum coseismic extensional strain is 40 ppm. Our analysis of GPS data in the region suggests that the postseismic decay of the 2007 Bengkulu earthquake was 46 days, estimated using a logarithmic function.